/s/ Aspiration in Masculine and Feminine speech of Limans in the United States - Bernate, Emily (Íkala, Revista de Lenguaje y Cultura, 2016)
This pilot study analyzes (s) aspiration in the speech of men and women from Lima, Peru. Firstly, it seeks to determine if men aspirate more than women of the same social class. Secondly, it aims to ascertain if women prioritize careful speech more than men by suppressing (s) aspirations. Six sociolinguistic interviews were conducted, and the first and last five minutes of each interview were analyzed for non-sibilant (s). Regarding the first hypothesis, men aspirated more than women throughout the interview. For the second research question, women demonstrated a marked difference between percentage of aspiration at the beginning and end of the interview, while men did not. The female participants aspirated infrequently at the beginning, but, after becoming more comfortable, increased in aspiration in the final portion of the interview. Both results were statistically significant to p < .05. These results corroborate other investigations which associate informal speech patterns with male speakers. Furthermore, these findings suggest that female speakers are more conscious of stylistic variation and use linguistic tools to differentiate between careful and informal speech styles.